1986
DOI: 10.1677/joe.0.1100043
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the vitamin D content of maternal milk and the vitamin D status of nursing women and breast-fed infants

Abstract: This work was designed to study the effect of the vitamin D content of human milk on the vitamin D status of exclusively breast-fed infants, and the relation between milk and maternal serum concentrations of vitamin D during the first month of lactation. Serum levels of calcium (Ca), phosphorus (P), magnesium (Mg) and 25-hydroxyvitamin D (25-OH-D) were determined in a racially heterogeneous population of nursing women, between days 3 and 5 (L3), 15 and 18 (L15) and 30 and 45 (L30) post partum. The same paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 23 publications
2
42
0
2
Order By: Relevance
“…Observational cohort studies (145,731,862,893) and randomized interventional trials (13,14,60,402,453,672,780,788,789,965) have not shown any effect of higher 25OHD concentrations or vitamin D supplementation to alter maternal mineral or skeletal homeostasis in otherwise healthy, lactating women across a broad range of vitamin D intakes and 25OHD levels. Vitamin D supplementation raises maternal 25OHD levels with a similar dose-response effect as in nonpregnant or nonlactating women.…”
Section: Human Datamentioning
confidence: 97%
See 1 more Smart Citation
“…Observational cohort studies (145,731,862,893) and randomized interventional trials (13,14,60,402,453,672,780,788,789,965) have not shown any effect of higher 25OHD concentrations or vitamin D supplementation to alter maternal mineral or skeletal homeostasis in otherwise healthy, lactating women across a broad range of vitamin D intakes and 25OHD levels. Vitamin D supplementation raises maternal 25OHD levels with a similar dose-response effect as in nonpregnant or nonlactating women.…”
Section: Human Datamentioning
confidence: 97%
“…Although milk vitamin D and 25OHD content are low, there is a correlation between milk 25OHD and neonatal 25OHD after the first month of lactation, indicating that despite its low content of vitamin D, breast milk is an important determinant of neonatal vitamin D stores (145,540,780). The estimated half-life of 25OHD in infants is 2-3 wk (717), similar to values in adults (59,62,189,344,449), which means that a higher cord blood 25OHD will only influence neonatal levels over about the first 6 wk.…”
Section: Human Datamentioning
confidence: 99%
“…[71][72][73][74]126 In a lactating mother supplemented with 400 IU/day of vitamin D, the vitamin D content of her milk ranges from Ͻ25 to 78 IU/L. 73,74,[126][127][128][129] Infants who are exclusively breastfed but who do not receive supplemental vitamin D or adequate sunlight exposure are at increased risk of developing vitamin D deficiency and/or rickets. 7,[10][11][12]14,18,81,130 Infants with darker pigmentation are at greater risk of vitamin D deficiency, 131 a fact explained by the greater risk of deficiency at birth 132 and the decreased vitamin D content in milk from women who themselves are deficient.…”
Section: The Effect Of Maternal Vitamin D Supplementation During Lactmentioning
confidence: 99%
“…7,[10][11][12]14,18,81,130 Infants with darker pigmentation are at greater risk of vitamin D deficiency, 131 a fact explained by the greater risk of deficiency at birth 132 and the decreased vitamin D content in milk from women who themselves are deficient. 127 A …”
Section: The Effect Of Maternal Vitamin D Supplementation During Lactmentioning
confidence: 99%
“…The mother's plasma 25(OH)D levels were 829 nmol/L (reference range 25-104 nmol/L), with the serum calcium of 3.61 mmol/L, serum phosphorous of 1.21 mmol/L, and alkaline phosphatase of 82 IU/L. 13 Vitamin D intake was stopped and the baby was given artificial formula. The infant's serum calcium normalized in 14 weeks.…”
Section: Casementioning
confidence: 99%